The clinical method and the scientific method - José Arteaga Herrera; José A Fernández Sacasas (Medisur)
This paper is the chapter dedicated to the scientific method and the clinical method in the authors’ Handbook “Teaching of Clinics”. Philosophycal principles of the scientific method and its stages are presented as well as the clinical method as a scientific one and its stages. A relationship between the clinical method and the medical record is established, the role of technology in the clinical method is stated and the most frequent mistakes when applying it in clinical practice are provided. Finally, the teaching of the clinical method and the appropriate settings to do it are discussed.